2016
DOI: 10.1128/mbio.02094-15
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Arginine Methyltransferase 1 (PRMT1) Is Necessary for Centrosome Dynamics during Tachyzoite Cell Division

Abstract: The arginine methyltransferase family (PRMT) has been implicated in a variety of cellular processes, including signal transduction, epigenetic regulation, and DNA repair pathways. PRMT1 is thought to be responsible for the majority of PRMT activity in Toxoplasma gondii, but its exact function is unknown. To further define the biological function of the PRMT family, we generated T. gondii mutants lacking PRMT1 (Δprmt1) by deletion of the PRMT1 gene. Δprmt1 parasites exhibit morphological defects during cell div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Surprisingly, Δisc3 parasites are completely avirulent in vivo , as mice were completely resistant to dosages of up to 10 6 knockout parasites, whereas the type I parental strain has an LD 100 = 1 in mice. This is in contrast to various other type I knockouts that have fitness defects and produce significantly smaller plaques in vitro yet are still able to kill mice with low doses of parasites, albeit sometimes with a delay in the time of death (Blume et al ., ; Shen, Buguliskis, Lee, & Sibley, ; Hammoudi et al ., ; El Bissati et al ., ; Pszenny et al , ). This discrepancy between the in vitro and in vivo phenotypes of Δisc3 parasites may reflect a reduced capacity of these knockouts to establish a productive infection upon intraperitoneal injection into mice.…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, Δisc3 parasites are completely avirulent in vivo , as mice were completely resistant to dosages of up to 10 6 knockout parasites, whereas the type I parental strain has an LD 100 = 1 in mice. This is in contrast to various other type I knockouts that have fitness defects and produce significantly smaller plaques in vitro yet are still able to kill mice with low doses of parasites, albeit sometimes with a delay in the time of death (Blume et al ., ; Shen, Buguliskis, Lee, & Sibley, ; Hammoudi et al ., ; El Bissati et al ., ; Pszenny et al , ). This discrepancy between the in vitro and in vivo phenotypes of Δisc3 parasites may reflect a reduced capacity of these knockouts to establish a productive infection upon intraperitoneal injection into mice.…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, an atypical kinase called MAPK‐Like and an arginine methyltransferase 1 were found associated with the PCM in T. gondii (El Bissati et al, ; Suvorova et al, ). Functional analysis revealed that MAPK‐like is required for proper daughter cell budding and mitosis while the arginine methyltransferase 1 PRMT1 is involved in the budding process and maintenance of centrosome stoichiometry (El Bissati et al, ; Suvorova et al, ). Finally, TgCDPK7 is required for centrosomal positioning and integrity (Morlon‐Guyot et al, ) (Figure B).…”
Section: Centrosome Biogenesismentioning
confidence: 99%
“…Changes in transcription occur during life cycle transitions (26) and PTMs are important regulators of the T. gondii cell cycle (27). In previous work, we identified multiple monomethylated arginine residues on T. gondii histones (28,29). T. gondii, encodes five PRMTs, four of which are predicted to be type I PRMTs and one that is predicted to be a type II enzyme, based on sequence similarity to human homologues (supplemental Table S1).…”
mentioning
confidence: 99%
“…T. gondii, encodes five PRMTs, four of which are predicted to be type I PRMTs and one that is predicted to be a type II enzyme, based on sequence similarity to human homologues (supplemental Table S1). Two of the type I PRMTs, TgPRMT1 and TgPRMT4, possess protein arginine methyltransferase activity and modify histones (29,30). Tg-PRMT4 localizes to the nucleus of the parasite where it has been implicated in gene regulation and parasite development (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation